Analysis of Factors Influencing the Choice of Inventory Accounting Methods in Manufacturing Companies Listed On the Bei - Angelica Faustine; Fidela Aldora; Siti Dini; Mhd Zulkifli Hasibuan (Britain International for Academic Research (BIAR) Publisher, 2024)
This research was created to obtain research objectivesFactors influencing the choice of inventory accounting methods in manufacturing companies listed on the IDX in the industrial and chemical sector in 2019-2021. This research uses quantitative research. The population in this research is allmanufacturing companies listed on the IDX in the industrial and chemical sector in 2019-2021as many as 16 and the research sample was 48 samples. The partial research results conclude that Inventory has a positive and significant effect on the Inventory Accounting Method, Cost of goods manufactured has no and significant effect on the Inventory Accounting Method, Gross profit margin has no and no significant effect on the Inventory Accounting Method, k Liquidity has a significant and significant effect on the Inventory Accounting Method . Simultaneously, inventory, cost of production, gross profit margin and liquidity have a positive and significant effect on the Inventory Accounting Method.